Integrating Islamic Character Values into the Teaching–Learning Process: Strategies, Implementation, and Effectiveness - Angga As'ari, M.; Darmansyah, Rafik (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study is motivated by an academic concern regarding the inconsistent understanding and implementation of Islamic character values in public schools, including SMPN 18 Kota Jambi, despite the national curriculum’s strong emphasis on character education. The research aims to describe how Islamic character values are integrated into the learning process and to analyze the strategies, strengths, and challenges encountered by teachers during implementation. A qualitative descriptive approach was employed, involving principals, teachers, and students through observations, interviews, and documentation. The findings indicate that Islamic values are integrated through teacher role modeling, reinforcement of religious routines, contextualization of learning materials, and habituation of positive behaviors within classroom interactions. These efforts are supported by the school’s commitment and teacher enthusiasm, yet challenges persist, particularly regarding limited facilities, diverse student characteristics, and the need for continuous professional development. The results imply that strengthening school culture, enhancing teacher pedagogical competence, and maintaining consistent character programs are essential to ensure sustainable and meaningful implementation of Islamic character education.